Decision mode, information and network attachment in the internationalization of SMEs: A configurational and contingency analysis - John Child; Linda H. Y. Hsieh (University of Birmingham, Birmingham Business School, 2013)
There has been limited attention to the internationalization of SMEs as a decision, and how the application of contrasting decision modes is associated with different information use and patterns of network attachment. This paper offers a new and systematic analysis of the likely associations between decision modes, information use, and network attachment among internationalizing SMEs. The analysis is applied to three categories of SME, identified in terms of their knowledge domain. By focusing on the relation between a relatively neglected subject - decision modes - and other issues that have been more centre-field, the paper contributes to an analytic synthesis in the field of SME research.
Keywords: 330; decision-making; information; SME knowledge domain; network attachment; internationalization